Lithium ion battery and electronic device
By leaving space in the packaging film punch of the lithium-ion battery, the problem of deformation and wrinkle of the battery cell during the charging and discharging cycle is solved, and the cycle stability and product advantage of the battery are improved.
Patent Information
- Application Number
- CN202411839334.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-11
- Publication Date
- 2025-03-18
AI Technical Summary
In lithium-ion batteries, the battery cell caused by the winding process has deformation and wrinkle problems during the charge and discharge cycle, especially the volume expansion of the silicon-containing negative electrode sheet is more serious, affecting the cycle stability of the battery.
By leaving space in the punching pit of the outer packaging film, it can alleviate the volume expansion of the battery cell, improve the deformation of the battery cell, and improve the circulation stability of the entire battery. The specific method is to adjust the gap between the battery cell and the packaging film punch to ensure that the width of the half-charged full battery meets specific conditions, and thus optimize the structure of the battery cell.
It effectively alleviates the deformation of the battery cell, improves the circulation stability of the entire battery, and improves the product's advantage.
Smart Images

Figure CN119650988A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery and an electronic device. Background Art
[0002] Soft-package lithium-ion batteries usually include battery cells and packaging films, among which the winding process for battery cells is widely used in the field of lithium-ion batteries due to its high production efficiency. However, the electrode sheets used for winding in the winding process are relatively long (usually greater than 40 cm), and the positive and negative electrode sheets expand in different degrees during the charge and discharge cycle, especially the volume expansion of silicon-containing negative electrode sheets is more serious, so that the wound battery cells have deformation and wrinkles after the formation capacity test. However, since the silicon-containing negative electrode sheet has a higher unit volume capacity, it is the most promising negative electrode sheet for the next generation of lithium-ion batteries. Therefore, it is very important to improve the expansion and deformation problems of lithium-ion batteries, especially lithium-ion batteries with silicon-containing negative electrode sheets. Summary of the invention
[0003] In view of the problem of expansion and deformation of the battery cells in the above-mentioned lithium-ion batteries, the present invention provides a lithium-ion battery and a method for preparing the same, which effectively improves the deformation of the battery cells and improves the cycle stability of the entire battery by reserving space in the punch holes of the outer packaging film (packaging film) to alleviate the expansion.
[0004] To this end, the present invention provides a lithium ion battery, which includes a battery cell, an electrolyte and a packaging film, wherein the battery cell is formed by a positive electrode sheet and a negative electrode sheet separated by a separator and wound, and the lithium ion battery is half-charged to obtain a half-charged full battery, and the packaging film is removed from the half-charged full battery to obtain a half-charged cell,
[0005] When the width of the half-charged battery is w1, the width of the half-charged cell is w2, and g=w2 / w1, the following condition (1) is satisfied:
[0006] 0.4< g <0.997 (1);
[0007] Furthermore, the negative electrode plate comprises a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2):
[0008] 420 mAh / cm 3 <g × a<2300 mAh / cm 3 (2)
[0009] Among them, 619mAh / cm 3 <a<3620mAh / cm 3 .
[0010] Specifically, the width w1 of the half-charged full battery refers to the minimum width of the half-charged full battery (including packaging film and battery cell) obtained after the lithium-ion battery is half-charged, usually measured with a vernier caliper; the width w2 of the half-charged battery refers to the maximum distance between the left corner and the right corner of the outermost circle of the battery cell after the packaging film is removed from the half-charged full battery, usually measured with a vernier caliper. When the number of winding layers and the width of the battery cell are constant, the gap between the battery cell and the punching hole of the packaging film is adjusted according to the volume expansion degree of the negative electrode plate, and then the width of the half-charged full battery is adjusted, which can effectively alleviate the volume expansion and improve the deformation of the battery cell, improve the cycle stability of the full battery, and improve the product quality rate.
[0011] In the lithium-ion battery of the present invention, the silicon-based material preferably includes at least one of nano-silicon, silicon oxide, silicon-carbon composite material or silicon alloy material.
[0012] In the lithium-ion battery of the present invention, the silicon-based material is preferably in a granular form, and its average particle size is preferably 500 nm to 30 μm.
[0013] In the lithium-ion battery of the present invention, the nano-silicon is preferably in a granular form, and its average particle size is preferably less than 100 nm.
[0014] The lithium-ion battery of the present invention, wherein the silicon oxide is preferably SiO X , where 0.6≤x≤2.
[0015] In the lithium-ion battery of the present invention, the positive electrode active material of the positive electrode plate is preferably selected from at least one of the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.
[0016] In the lithium-ion battery of the present invention, the separator is preferably selected from at least one of the group consisting of polyethylene, polypropylene and polyvinylidene fluoride.
[0017] In the lithium-ion battery of the present invention, the packaging film is preferably an aluminum-plastic film.
[0018] In the lithium-ion battery of the present invention, the packaging film preferably has a thickness of 67 to 153 μm and a tensile strength of 4 to 10 N / mm.
[0019] The present invention also provides a method for preparing a lithium ion battery, comprising the following steps:
[0020] S1. Mixing the positive electrode active material with the conductive agent, the binder and the solvent to form a mixed slurry, coating the mixed slurry on the substrate, and obtaining the positive electrode sheet after drying, cold pressing and slitting;
[0021] S2, mixing the negative electrode active material with the conductive agent, the binder and the solvent to form a mixed slurry, coating the mixed slurry on the substrate, and obtaining the negative electrode sheet after drying, cold pressing and slitting;
[0022] S3, stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, and then winding them to obtain a battery cell; and
[0023] S4, put the battery cell into the packaging film, inject the electrolyte after drying and seal it, and obtain the full battery after formation, degassing and trimming.
[0024] After the full battery is half-charged, a half-charged full battery is obtained. After the packaging film is removed from the half-charged full battery, a half-charged cell is obtained. When the width of the half-charged full battery is w1, the width of the half-charged cell is w2, and g=w2 / w1, the following conditional formula (1) is satisfied:
[0025] 0.4< g <0.997 (1);
[0026] Furthermore, the negative electrode active material of the negative electrode plate comprises a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2):
[0027] 420 mAh / cm 3 <g × a<2300 mAh / cm 3 (2)
[0028] Among them, 619mAh / cm 3 <a<3620mAh / cm 3 .
[0029] The present invention also provides an electronic device, which includes: the above-mentioned lithium-ion battery.
[0030] The lithium-ion battery and preparation method thereof provided by the present invention adjust the gap between the battery cell and the punching hole of the packaging film according to the volume expansion degree of the negative electrode plate, and then adjust the width of the half-charged full battery, which can effectively alleviate the volume expansion and thus improve the deformation of the battery cell, improve the cycle stability of the full battery, and increase the quality rate of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the cross-sectional structure of a half-charged full battery of the present invention;
[0032] Figure 2 The battery cell of Example 6 after 100 cycles (the Ripple value of the battery corresponding to the measured battery cell is 0.8%);
[0033] Figure 3This is the battery cell of Comparative Example 4 after 100 cycles (the Ripple value of the battery corresponding to the measured battery cell is 7.2%);
[0034] Figure 4 This is the battery cell of Comparative Example 1 after 100 cycles (the Ripple value of the battery corresponding to the measured battery cell is 5.8%).
[0035] Reference numerals:
[0036] 1. Punching pit; 2. Packaging film; 3. Gap;
[0037] w1, width of a half-charged battery; w2, width of a half-charged cell. DETAILED DESCRIPTION
[0038] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0039] I. Definition of terms
[0040] 1. Wrinkles and deformation
[0041] In the present invention, wrinkles refer to the phenomenon of continuous bending of the isolation membrane and the positive / negative electrode sheets; deformation refers to: deformation occurs when Ripple>2%, and severe deformation occurs when Ripple>4%, where Ripple=flat surface thickness of the whole battery (PPG) / point thickness of the whole battery (MMC)-1.
[0042] 2. Half charge
[0043] Definition: A full battery charged to the range of 3.7V to 4.0V is called a half-charged full battery; the process is called half-charging.
[0044] 2. Battery performance test:
[0045] 1. Full battery deformation test:
[0046] PPG is defined as the flat surface thickness of the whole battery. The thickness is measured using a cell flat plate thickness gauge. The whole battery is placed inside a 700g PPG plate, and the surface thickness of the whole battery is measured three times in sequence, and the average of the three data is taken. MMC is defined as the point thickness of the whole battery. Three points are taken at intervals along the vertical direction of the Al tab below the tab, and the thickness is measured with a micrometer and the average value is taken. Ripple is defined as PPG / MMC-1, and the thickness data of the whole battery after 100 cycles is taken as the judgment point. When Ripple>2%, deformation occurs, and Ripple>4% is severe deformation.
[0047] 2. Full cell cycle performance test:
[0048] High temperature cycle test: The test temperature is 45°C. Charge at a constant current of 0.7C to 4.4V, then charge at a constant voltage until the current reaches 0.025C. After standing for 5 minutes, discharge at 0.5C to 3.0V. The capacity obtained in this step is used as the initial capacity. Perform a cycle test with 0.7C charge / 0.5C discharge. By taking the ratio of the capacity of each step to the initial capacity, a capacity decay curve can be obtained. The battery cycle performance of the present invention is illustrated by counting the number of cycles when the capacity decays to 80% of the initial capacity.
[0049] III. Specific examples and comparative examples
[0050] Example 1
[0051] Preparation of full cell
[0052] (1) Mix the cathode active material LiCoO2, conductive carbon black, and binder polyvinylidene fluoride (PVDF) in a weight ratio of 96.7:1.7:1.6 in an N-methylpyrrolidone solvent system, stir well and mix evenly, then coat it on an Al foil. After drying, cold pressing, and slitting, a cathode electrode sheet is obtained.
[0053] (2) Mix commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5μm) with graphite to obtain the anode active material. The proportion of commercial silicon oxide SiO X in the anode active material is 0 - 5 wt%. Mix the anode active material, conductive agent acetylene black, and polyacrylic acid (PAA) in a weight ratio of 95:1.2:3.8 in a deionized water solvent system, stir well and mix evenly, then coat it on a Cu foil, dry, cold press, and slit to obtain an anode electrode sheet;
[0054] When coating the anode active material on the Cu foil above, the coating weight is 9.74 mg / cm 2 , control the proportion of commercial silicon oxide SiO X in the anode active material to select a definite value within 0 - 5 wt%, so that the capacity a per unit volume of the anode electrode sheet is 619.8 mAh / cm 3 .
[0055] (3) Use a polyethylene (PE) porous polymer film as the separator. Stack the cathode electrode sheet, separator, and anode electrode sheet in sequence, with the separator in the middle of the cathode and anode to play a separation role, and wind to obtain an electric core.
[0056] (4) Preparation of electrolyte: In a dry argon environment, lithium hexafluorophosphate (LiPF6) was added to a solvent solution prepared by mixing propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) in a weight ratio of 1:1:1 and mixed evenly. The concentration of LiPF6 was about 1.15 mol / L. Then, 12 wt% of fluoroethylene carbonate (FEC) was added and mixed evenly to obtain the electrolyte.
[0057] (4) The battery cell was encapsulated into the pit 1 of the packaging film 2 (the aluminum-plastic film includes an outer layer of nylon, a middle layer of Al, and an inner layer of PP, and its thickness and strength are shown in Table 1), dried, injected with electrolyte and encapsulated, and then a full cell was obtained through formation, degassing, and edge trimming.
[0058] By controlling the gap 3 between the battery cell and the pit, the width of the full cell after half charge was w1 = 15.7 mm, and the width of the battery cell after half charge was w2 = 15.6 mm. At this time, g = 0.99, and g×a = 613.6 mAh / cm 3 . Among them
[0059] After obtaining the above lithium-ion full cell, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0060] Example 2
[0061] The capacity a per unit volume of the negative electrode sheet was also 619.8 mAh / cm 3 , which was different from Example 1 in that during encapsulation, the inner pit width of the pit 1 of the packaging film 2 was controlled to be w1 = 36.7 mm, and the width of the battery cell was w2 = 36.1 mm. At this time, g = 0.98, and g×a = 607.4 mAh / cm 3 .
[0062] After obtaining the above lithium-ion full cell, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0063] Example 3
[0064] The difference from Example 1 was that
[0065] Commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) was mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material was 10 - 15 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) were fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on the Cu foil, dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0066] When coating the negative electrode active material on the Cu foil, the coating weight is 7.27 mg / cm 2 , control the proportion of commercial silicon oxide SiO X in the negative electrode active material to select a definite value within 10-15 wt%, so that the capacity a per unit volume of the negative electrode sheet is 957.8 mAh / cm 3 .
[0067] During encapsulation, control the inner pit width of the pit 1 of the packaging film 2 to be w1 = 17.1 mm, and the width of the battery cell to be w2 = 16.5 mm. At this time, g = 0.96, and g×a = 919.5 mAh / cm 3 .
[0068] After obtaining the above lithium-ion full battery, perform battery performance tests, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0069] Example 4
[0070] The capacity a per unit volume of the negative electrode sheet is also 957.8 mAh / cm 3 , the difference from Example 3 is that during encapsulation, control the inner pit width of the pit 1 of the packaging film 2 to be w1 = 37.2 mm, and the width of the battery cell to be w2 = 36.2 mm. At this time, g = 0.97, and g×a = 929.1 mAh / cm 3 .
[0071] After obtaining the above lithium-ion full battery, perform battery performance tests, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0072] Example 5
[0073] The difference from Example 1 is that
[0074] Mix commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material is 20-25 wt%. Then, stir and mix the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) evenly in a deionized water solvent system according to the weight ratio of 95:1.2:3.8, and then coat it on the Cu foil, dry it, cold press it, and cut it into strips to obtain the negative electrode sheet.
[0075] When coating the negative electrode active material on the Cu foil, the coating weight is 5.324 mg / cm 2 , control the commercial silicon oxide SiO XThe proportion of the negative electrode active material is selected to a certain value within 20-25wt%, so that the capacity a per unit volume of the negative electrode plate is 1151.3 mAh / cm 3 .
[0076] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=17.0 mm, and the width of the battery cell is w2=16.0 mm. At this time, g=0.94, g×a=1082.2 mAh / cm 3 .
[0077] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.
[0078] Example 6
[0079] The capacity per unit volume of the negative electrode is also 1151.3 mAh / cm 3 The difference from Example 5 is that during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=37.5 mm, and the width of the battery cell is w2=36.3 mm. At this time, g=0.97, g×a=1116.8 mAh / cm 3 .
[0080] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=36.0 mm, and the width of the battery cell is w2=36.0 mm. At this time, g=0.9992, g×a=619.3 mAh / cm 3 .
[0083] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.
[0084] Comparative Example 2
[0085] The difference from Example 3 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=16.54 mm, and the width of the battery cell is w2=16.5 mm. At this time, g=0.9975, g×a=955.4 mAh / cm 3 .
[0086] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.
[0087] Comparative Example 3
[0088] It is different from Example 5 in that during encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 44.5 mm, and the width of the battery cell is w2 = 15.6 mm. At this time, g = 0.35, and g×a = 403.0 mAh / cm 3 .
[0089] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0090] Example 7
[0091] It is different from Example 1 in that
[0092] Commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material is 30 - 35 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold-pressed, and slit to obtain a negative electrode sheet.
[0093] When coating the negative electrode active material on the Cu foil above, the coating weight is 5.324 mg / cm 2 , control the proportion of commercial silicon oxide SiO X in the negative electrode active material to select a definite value within 30 - 35 wt% so that the capacity a per unit volume of the negative electrode sheet is 1336.7 mAh / cm 3 .
[0094] During encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 17.9 mm, and the width of the battery cell is w2 = 15.9 mm. At this time, g = 0.89, and g×a = 1189.6 mAh / cm 3 .
[0095] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0096] Example 8
[0097] It is different from Example 1 in that
[0098] Commercial silicon oxide SiO X(0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material, and commercial silicon oxide SiO X accounts for 45 - 50 wt% of the negative electrode active material. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold-pressed, and slit to obtain the negative electrode sheet,
[0099] When coating the negative electrode active material on the Cu foil above, the coating weight is 4.181 mg / cm 2 , and control the proportion of commercial silicon oxide SiO X in the negative electrode active material to select a definite value within 45 - 50 wt% so that the capacity a per unit volume of the negative electrode sheet is 1671.8 mAh / cm 3 .
[0100] During encapsulation, control the inner pit width of the pit 1 of the packaging film 2 to be w1 = 40.7 mm, and the width of the battery cell to be w2 = 36.9 mm. At this time, g = 0.91, and g × a = 1521.3 mAh / cm 3 .
[0101] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0102] Example 9
[0103] The difference from Example 1 is that,
[0104] Commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material, and commercial silicon oxide SiO X accounts for 55 - 60 wt% of the negative electrode active material. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold-pressed, and slit to obtain the negative electrode sheet,
[0105] When coating the negative electrode active material on the Cu foil above, the coating weight is 3.265 mg / cm 2 , and control the proportion of commercial silicon oxide SiO X in the negative electrode active material to select a definite value within 55 - 60 wt% so that the capacity a per unit volume of the negative electrode sheet is 2006.6 mAh / cm 3 .
[0106] During encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 21.8 mm, and the width of the battery cell is w2 = 15.8 mm. At this time, g = 0.72, and g×a = 1444.8 mAh / cm 3 .
[0107] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0108] Example 10
[0109] The difference from Example 1 is that
[0110] Commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material is 80 - 85 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to the weight ratio of 95:1.2:3.8, and then coated on the Cu foil, dried, cold-pressed, and slit to obtain the negative electrode plate,
[0111] When coating the negative electrode active material on the Cu foil above, the coating weight is 2.640 mg / cm 2 , and the proportion of commercial silicon oxide SiO X in the negative electrode active material is selected to be a certain value within 80 - 85 wt% so that the capacity a per unit volume of the negative electrode plate is 2422.2 mAh / cm 3 .
[0112] During encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 78.0 mm, and the width of the battery cell is w2 = 70.0 mm. At this time, g = 0.89, and g×a = 2155.7 mAh / cm 3 .
[0113] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0114] Example 11
[0115] The difference from Example 1 is that
[0116] Commercial silicon oxide SiO X(0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiOx in the negative electrode active material is 90 - 95 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold-pressed, and cut into strips to obtain the negative electrode sheet.
[0117] When coating the negative electrode active material on the Cu foil above, the coating weight is 2.449 mg / cm 2 , and control the proportion of commercial silicon oxide SiO X in the negative electrode active material to select a definite value within 90 - 95 wt% such that the capacity a per unit volume of the negative electrode sheet is 2677.7 mAh / cm 3 .
[0118] During encapsulation, control the inner pit width of the pit 1 of the packaging film 2 to be w1 = 45.9 mm, and the width of the battery cell to be w2 = 35.9 mm. At this time, g = 0.78, and g × a = 2088.6 mAh / cm 3 .
[0119] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0120] Example 12
[0121] The difference from Example 1 is that
[0122] Commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material is 95 - 100 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold-pressed, and cut into strips to obtain the negative electrode sheet.
[0123] When coating the negative electrode active material on the Cu foil above, the coating weight is 2.337 mg / cm 2 , and control the proportion of commercial silicon oxide SiO X in the negative electrode active material to select a definite value within 95 - 100 wt% such that the capacity a per unit volume of the negative electrode sheet is 2839.0 mAh / cm 3 .
[0124] During encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 35.6 mm, and the width of the battery cell is w2 = 15.6 mm. At this time, g = 0.43, and g×a = 1220.8 mAh / cm 3 .
[0125] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0126] Example 13
[0127] The difference from Example 1 is that
[0128] Commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) is mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material is 95 - 100 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed evenly in a deionized water solvent system according to the weight ratio of 95:1.2:3.8, and then coated on the Cu foil, dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0129] When coating the negative electrode active material on the Cu foil above, the coating weight is 2.590 mg / cm 2 , and the proportion of commercial silicon oxide SiO X in the negative electrode active material is selected to be a certain value within 95 - 100 wt% so that the capacity a per unit volume of the negative electrode sheet is 3600 mAh / cm 3 .
[0130] During encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 35.6 mm, and the width of the battery cell is w2 = 15.0 mm. At this time, g = 0.42, and g×a = 1512.0 mAh / cm 3 .
[0131] After obtaining the above lithium-ion full battery, battery performance tests are carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0132] Comparative Example 4
[0133] The difference from Example 10 is that during encapsulation, the inner pit width of the pit 1 of the packaging film 2 is controlled to be w1 = 36.2 mm, and the width of the battery cell is w2 = 36.2 mm. At this time, g = 1, and g×a = 2422.2 mAh / cm 3 .
[0134] After obtaining the above lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0135] Comparative Example 5
[0136] The difference from Example 9 is that during encapsulation, the inner pit width of the pit 1 of the packaging film 2 was controlled to be w1 = 52.5 mm, and the width of the battery cell was w2 = 18.9 mm. At this time, g = 0.36, and g×a = 722.4 mAh / cm 3 .
[0137] After obtaining the above lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0138] Comparative Example 6
[0139] The difference from Example 1 is that
[0140] commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) was mixed with graphite to obtain the negative electrode active material. The proportion of commercial silicon oxide SiO X in the negative electrode active material was 11-20 wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) were fully stirred and mixed evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold-pressed, and slit to obtain a negative electrode plate.
[0141] When coating the negative electrode active material on the Cu foil above, the coating weight was 7.560 mg / cm 2 , and the proportion of commercial silicon oxide SiO X in the negative electrode active material was selected to be a certain value within 11-20 wt% so that the capacity a per unit volume of the negative electrode plate was 619.8 mAh / cm 3 .
[0142] During encapsulation, the inner pit width of the pit 1 of the packaging film 2 was controlled to be w1 = 36.35 mm, and the width of the battery cell was w2 = 36.3 mm. At this time, g = 0.43, and g×a = 266.5 mAh / cm 3 .
[0143] After obtaining the above lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 in detail.
[0144] Comparative Example 7
[0145] The difference from Comparative Example 6 is that
[0146] Mix commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) with graphite to obtain the anode active material. The proportion of commercial silicon oxide SiO X in the anode active material is 11 - 20 wt%. Then, stir and mix the anode active material, conductive agent acetylene black, and polyacrylic acid (PAA) evenly in a deionized water solvent system according to a weight ratio of 95:1.2:3.8, and then coat it on a Cu foil, dry it, cold press it, and cut it into strips to obtain the anode electrode sheet.
[0147] When coating the anode active material on the Cu foil, the coating weight is 7.130 mg / cm 2 , control a definite value within the range of 11 - 20 wt% for the proportion of commercial silicon oxide SiO X in the anode active material, so that the capacity a per unit volume of the anode electrode sheet is 957.8 mAh / cm 3 .
[0148] During encapsulation, g × a = 411.9 mAh / cm 3 .
[0149] After obtaining the above lithium-ion full battery, conduct battery performance tests, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0150] Comparative Example 8
[0151] The difference from Example 13 is that
[0152] During encapsulation, control the inner pit width of the pit 1 of the packaging film 2 to be w1 = 16.46 mm, and the width of the battery core to be w2 = 16.4 mm. At this time, g = 0.996, and g × a = 3585.6 mAh / cm 3 .
[0153] After obtaining the above lithium-ion full battery, conduct battery performance tests, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1 for details.
[0154] Comparative Example 9
[0155] The difference from Example 1 is the thickness and tensile strength of the packaging film 2, as shown in Table 1 for details.
[0156] In addition, mix commercial silicon oxide SiO X (0.5 < x < 1.5, DV50 = 5 μm) with graphite to obtain the anode active material. The commercial silicon oxide SiO XThe proportion of the negative electrode active material is 80-85wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.
[0157] When the negative electrode active material is coated on the Cu foil, the coating weight is 2.640 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 80-85wt%, so that the capacity a per unit volume of the negative electrode plate is 2422.0 mAh / cm 3 .
[0158] When encapsulated, g×a=2397.8mAh / cm 3 .
[0159] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.
[0160] Comparative Example 10
[0161] The difference from Comparative Example 9 is the thickness and tensile strength of packaging film 2, see Table 1 for details.
[0162] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.
[0163] Table 1
[0164]
[0165]
[0166] See Table 1, where the Ripple value is the value after 100 cycles. When Ripple>2%, deformation occurs, and Ripple>4% is severe deformation; the test method of the unit volume capacity a is as follows: the negative electrode plate (single-sided area) obtained in the embodiment is measured with a micrometer to measure the single-sided plate and the corresponding copper foil thickness (t1 and t2, respectively), and dried in a vacuum drying oven at 85°C for 12 hours. Then, it is cut into discs with a diameter of 1.4 cm by a punch in a dry environment. In a glove box, a metal lithium sheet is used as the counter electrode, and a ceglard composite film is selected as the isolation membrane. The electrolyte is added to assemble a button cell. The battery is charged and discharged using the LAND series battery test to test its charge and discharge performance. The capacity obtained is set to C1 (mAh), then the unit volume capacity a = C1*unit area coating weight / (t1-t2).
[0167] First, as demonstrated by the comparison between Examples 1-6 and Comparative Examples 1-3, when the unit volume capacity of the negative electrode sheet is the same, controlling different g values will result in different degrees of deformation.
[0168] Specifically, through the grouped comparison of Example 4 with Comparative Example 2, and Example 6 with Comparative Example 3, it is found that on the premise of the same unit volume capacity, too large or too small g values have a significant impact on the deformation of the battery cell and the cycle stability of the battery.
[0169] Furthermore, through the grouped comparison of Example 1 and 2 with Comparative Example 1, Example 3 and 4 with Comparative Example 2, and Example 5 and 6 with Comparative Example 3, it is found that under the condition of the same unit volume capacity of the negative electrode sheet, when the g value is greater than 0.997 or less than 0.4, the battery cell undergoes severe deformation. When the g value is greater than 0.997, it indicates that the gap between the battery cell and the indentation is small, insufficient to relieve the volume expansion of the battery cell. As shown in Comparative Examples 1-2, the battery cell undergoes severe deformation. When g is less than 0.4, as in Comparative Example 3, it indicates that the gap between the battery cell and the indentation is large. On the one hand, when the amount of electrolyte is fixed, the space for it to infiltrate the battery cell decreases, and the solid electrolyte interface (SEI) deteriorates, thus worsening the cycle performance. On the other hand, it makes the mobility of the battery cell in the indentation larger, affecting the safety of the battery cell. In addition, for a severely deformed battery cell, its battery cycle performance also deteriorates significantly. This is because the severe deformation of the battery cell creates voids between the electrode and the separator, forms microcracks on the electrode sheet, and the solid electrolyte interphase (SEI) film ruptures and reorganizes, consuming the electrolyte, thereby deteriorating the cycle performance of the battery.
[0170] Second, through the comparison of Example 12 with Comparative Examples 6 and 7, it is found that when the g value is the same, but the unit volume capacity a of the negative electrode sheet is different, there are also significant differences in the deformation of the battery cell and the cycle stability of the battery. Therefore, for different unit volume capacities a of the negative electrode sheet, different g values need to be matched to relieve volume expansion to further optimize the deformation of the battery cell and the cycle stability of the battery. And, as can be seen from Comparative Examples 6 and 7, when the g value is in the range of 0.4 < g < 0.997, but g×a is less than 420 mAh / cm 3 , the battery cell shows a severe deformation phenomenon; similarly, when the g value is in the range of 0.4 < g < 0.997, but g×a is greater than 2300 mAh / cm 3 , the battery cell also shows severe deformation, as shown in Comparative Example 8. That is to say, the degree of volume expansion caused by different unit volume capacities a of the negative electrode sheet is also different. Therefore, different gaps (i.e., the voids between the battery cell and the indentation of the packaging film) need to be set according to different unit volume capacities a to relieve volume expansion to the greatest extent and achieve the optimal utilization of space.
[0171] In summary, the g value is a major factor affecting the deformation of the battery cell after cycling. At the same time, different specific capacities a per unit volume of the negative electrode tab need to match different g values to optimize the structure of the battery cell. When the specific capacity a per unit volume of the negative electrode tab is between 619 mAh / cm 3 <a < 3620 mAh / cm 3 and the g value is set between 0.4 < g < 0.997, and g×a is between 420 mAh / cm 3 <g×a < 2300 mAh / cm 3 the deformation of the battery cell and the cycle stability of the battery can be greatly improved. This shows that starting from the optimization of the battery cell structure, reserving corresponding space according to different specific capacities a per unit volume can effectively relieve volume expansion, thereby improving the deformation of the battery cell and the cycle stability of the battery, and thus improving the yield of the product.
[0172] In addition, referring to Table 1, it can be seen from Comparative Examples 9-10 that the thickness and strength of the aluminum-plastic film have a certain impact on the deformation of the battery cell and the subsequent cycling of the battery. If the aluminum-plastic film is too thin, the tensile strength is insufficient, resulting in a certain deformation of the battery cell after cycling; while if the aluminum-plastic film is too thick, although there is no obvious deformation of the battery cell and attenuation of the battery cycling performance, considering the volume specific capacity of the full battery, since the volume of the aluminum-plastic film also participates in the composition of the total volume, the volume specific capacity of the full battery will decrease to a certain extent.
[0173] Of course, the present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations should all fall within the protection scope of the present invention.
Claims
1. A lithium-ion battery, comprising a battery cell, an electrolyte and a packaging film, wherein the battery cell is formed by winding a positive electrode sheet and a negative electrode sheet separated by a separator, and the lithium-ion battery is half-charged to obtain a half-charged full battery, and the packaging film is removed from the half-charged full battery to obtain a half-charged battery, characterized in that: When the width of the half-charged battery is w1, the width of the half-charged cell is w2, and g=w2 / w1, the following condition (1) is satisfied: 0.43< g <0.997 (1); Furthermore, the negative electrode plate comprises a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2): 420 mAh / cm 3 <g × a<2300 mAh / cm 3 (2), Among them, 619mAh / cm 3 <a<2839.0mAh / cm 3 .
2. The lithium-ion battery according to claim 1, characterized in that The silicon-based material includes at least one of nano-silicon, silicon oxide, silicon-carbon composite material or silicon alloy material.
3. The lithium-ion battery according to claim 1, characterized in that The silicon-based material is in granular form, and its average particle size is 500nm-30μm.
4. The lithium-ion battery according to claim 2, characterized in that: The nano silicon is in particle form, and its average particle size is less than 100 nm.
5. The lithium-ion battery according to claim 2, characterized in that: The silicon oxide is SiO X , where 0.6≤x≤2.
6. The lithium-ion battery according to claim 1, characterized in that The positive electrode active material of the positive electrode plate is at least one selected from the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.
7. The lithium-ion battery according to claim 1, characterized in that: The diaphragm is selected from at least one of the group consisting of polyethylene, polypropylene and polyvinylidene fluoride.
8. The lithium-ion battery according to claim 1, characterized in that The packaging film is an aluminum-plastic film.
9. The lithium-ion battery according to claim 1, characterized in that: The packaging film has a thickness of 67 to 153 μm and a tensile strength of 4 to 10 N / mm.
10. The lithium ion battery according to claim 1, characterized in that: 0.72<g<0.997。 11. The lithium ion battery according to claim 1, characterized in that: 0.89<g<0.997。 12. An electronic device, characterized in that: Comprising: the lithium ion battery according to any one of claims 1 to 11.